Cost-Effectiveness of Vitamin D Supplementation in Pregnant Woman and Young Children in Preventing Rickets: A Modeling Study - Floreskul, Vilius; Juma, Fatema Z.; Daniel, Anjali B.; Zamir, Imran; Rawdin, Andrew; Stevenson, Matthew; Mughal, Zulf; Padidela, Raja (Frontiers in Public Health, 2020)
Background Literature on the cost of management of rickets and cost-effectiveness of vitamin D supplementation in preventing rickets is lacking. Methods This study considered the cost-effectiveness of providing free vitamin D supplementation to pregnant women and children less than four years of age with varying degrees of skin pigmentation to prevent rickets in children. Estimates for the prevalence of rickets were calculated using all cases of rickets diagnosed in Central Manchester, UK and census data from the region. Cost of management of rickets were calculated using National Health Service, UK tariffs. The efficacy of vitamin D supplementation was based on a similar programme implemented in Birmingham. Quality of life was assessed using utility estimates derived from a systematic literature review. In this analysis the intervention was considered cost-effective if the incremental cost-effectiveness ratio (ICER) is below the National Institute for Health and Care Excellence, UK cost-effectiveness threshold of £20,000 per Quality-adjusted life year (QALY). Results Fifty-seven patients (26 dark, 29 medium and 2 light skin tones) were managed for rickets and associated complications over 4-years. Rickets has an estimated annual incidence of 29·75 per 100,000 children less than four years of age. In the dark skin tone population vitamin D supplementation proved to be cost saving. In a medium skin tone population and light skin tone populations the ICER was £19,295 per QALY and £404,047 per QALY respectively. Conclusion Our study demonstrates that a vitamin D supplementation to prevent rickets is cost effective in dark and medium skin tone populations.